Public Participation in Maine’s Environmental Policy: Opportunities to Strengthen Inclusivity - Brown, Allison; Lai, Kimberly; Victor, Erin; Venne, Gabrielle; Rahman, Ashik; Isenhour, Cindy; Webster, Katrina; Mardosa, Catherine (Maine Policy Review, 2025)
Maine is known for its progressive approach to environmental policy in part due to the state’s historical dependence on natural resources and rich biodiversity. As a whole, Mainers actively engage in local politics: regularly testifying at public hearings, contacting their elected officials, and submitting public comments. Participation helps create policies that reflect the will of the people, ensure that those affected by policies are able to voice their support and concerns, and safeguard against powerful special interest groups dominating policy construction. However, our analysis of the public comments on three recent pieces of environmental legislation – LD 1679, LD 1541, and LD 294 – suggest there is significant room for improvement. We argue that political participation in Maine could be further strengthened through greater inclusion of rural and Indigenous populations most susceptible to proposed legislation to ensure that the state continues to lead in environmental policy.